Penggunaan Metode Pembelajaran Jigsaw pada Pembelajaran Akidah Akhlak untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik - Amalina, Wildah (Indonesian Journal of Islamic Elementary Education, 2023)
Choosing the right learning method is very important to support the achievement of optimal learning outcomes. Therefore, the aim of this research is to determine the increase in activity and learning outcomes of class V.1 students in the Aqidah Morals subject matter Asma'ul Khusna Al Muhyi, Al Mumitu, and Al Ba'ist using the Jigsaw method. This type of research is Classroom Action Research carried out in Class V.1 at MSI XI Nurul Islam Pekalongan. This research was conducted in 2 cycles. The research data shows that there has been a change and increase in learning activities in the aspects of enthusiasm, activeness and responsibility in both cycle 1 and cycle 2. The increase in student learning outcomes is demonstrated by achieving completeness of student learning outcomes with Minimum Completeness Criteria (KKM) 70 of 62 .5% with an average score of 76.208 in cycle I. Meanwhile in cycle II, learning outcomes that reached KKM 70 were 91.67% with an average score of 80.083. The results of this research show that the use of the jigsaw method can improve students' activities and learning outcomes in learning moral beliefs in class V.1 MSI XI Nurul Islam Pekalongan for the 2022/2023 Academic Year.